Food products Assessment of quality - Koval, Olha; Guts, Viktor (My University, 2013)
The theory of kinetic modeling of the quality and shelf life of food products based on second differential order equations offers much more possibilities of the kinetics analysis of accumulating harmful substances in the product in comparison with existing methods of touch, opens new possibilities for the development of standards for their qualitative assessment of food quality.
Keywords: model of forecasting spoilage of food product; моделі прогнозування псування харчових продуктів; кафедра екології та екоменеджменту; кафедра технології ресторанної і аюрведичної продукції